Implementing electronic government procurement (e-GP) in Bangladesh: a study on 10 district LGED offices - Roy, Tirthajit (BRAC University, 2018)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2018.